(untitled) (The Proceedings of The International Conference on Climate Change, 2021)
The fast-urbanizing Indian cities are grappling with rising ecological challenges. Pollution, water insecurity, urban heat, and flooding have increased the vulnerability of the urban population. There is a need to look at urban settlements as a functioning natural ecosystem delineated by administrative boundaries and to evaluate their health regularly through a comprehensive, easy to adopt, structured approach. This study aims to track and evaluate the ecosystem health of three different categories of urban settlements: a group of metropolitan wards, a growing peripheral city, and an emerging town, through adaption of Pressure- State-Response (PSR) framework developed by the Organisation for Economic Co-operation and Development (OECD)’. The methodology includes indices-driven change detection of ecosystem components and pressure points on the same, by using spatial and non-spatial data, developing an impact matrix, and prioritized eco plans for action. Increasing built-up surfaces in the peripheral city (11%) and the metropolitan wards (23%) show increased pressure on their ecosystem in the form of reducing pervious surfaces. Increasing water turbidity, land surface temperatures, and aerosol content in the air depict pressure hotspots requiring mitigative, restorative, and preventive action. A significant decrease observed in heavy vegetation in the metropolitan onwards (58% in the last 5 years) and an increase in industrial activities and aerosol is observed in conjunction with increasing air temperatures and this points towards an impending change in its livability index due to anthropogenic pressures and climate change. The study concludes that a structured approach can aid in agile and sustainable management of our towns and cities and nature-based solutions provide an opportunity to restore the ecosystem balance.